"I hate Tuesdays!" The self-efficacy beliefs of postgraduate language practice students - Delport, M.C. (South African Journal of Higher Education, 2019)
The high drop-out and low throughput rates in higher educational institutions is a matter of concern. Students must overcome many psychological barriers in the pursuit of an under- and postgraduate qualification. Self-efficacy is regarded as an under-researched psychological variable that may impact on students’ success at tertiary level. Drawing on Bandura’s Social Cognitive Theory, this study explores the self-efficacy beliefs of postgraduate Language Practice students. A qualitative, exploratory and descriptive research design was used. Eleven narrative essays were completed and analysed by means of directive coding. Tuesdays were identified as the worst day of the week due to the module Research Methods and Techniques, that impacted negatively on the students’ self-efficacy beliefs. Social engagement in the form of support groups is seen as an important role player in self-efficacy beliefs. Educators should consider students’ various backgrounds when engaging with students, since this aspect proves to be an important factor in the development of self-efficacy beliefs. The findings may help navigate educators towards rendering the necessary emotional and social student support as a strategy to address the low success rate in universities.